Embodying the Swamp: Ecological Memory and Spatial Performance in Asmat Dance from Papua - Mustain Murda, Muhamad Ilham (Westscience Press, 2025)
This article investigates the relationship between ecological space and choreographic structure in the traditional dance of the Asmat people of Papua, Indonesia. Drawing on the concept of embodied geography, the study explores how bodily movements are formed in response to geographical terrain—particularly swamp environments—and preserved across generations through dance. Rather than conducting fieldwork in the remote Asmat region, the research uses a visual ethnographic approach by analyzing a recorded performance of Piri Jo Ciwewi by Asmat diaspora youth in Jayapura, and interviewing cultural practitioners from the Wowpits dormitory. Key insight was provided by Mikel Pombay, an alumnus of the Dance Department at the Indonesian Institute of Arts and Culture (ISBI) Tanah Papua, who originates from the Asmat community. His narratives contextualized bodily gestures in terms of ecological adaptation, spiritual relations, and cultural continuity. Movement analysis revealed distinctive gestures such as grounded postures, lateral weight shifts, and mimetic actions that mirror canoeing, forest navigation, and animal motion—each of which corresponds to swamp-based knowledge systems. The findings affirm that Asmat dance is not only a spiritual or aesthetic practice but a spatial archive that encodes environmental experience through the body. Even when performed in diaspora, such as in urban Jayapura, the dance retains its geographic logic. This research contributes to interdisciplinary understandings of indigenous performance, proposing that traditional dance acts as a medium of ecological memory and spatial resilience.